2021
DOI: 10.1016/j.radi.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose tracking in computed tomography: Red alerts and feedback. Implementing a radiation dose alert system in CT

Abstract: Introduction: This study investigates instances of elevated radiation dose on a radiation tracking system to determine their aetiologies. It aimed to investigate the impact of radiographer feedback on these alerts. Methods: Over two six-month periods 11,298 CT examinations were assessed using DoseWatch. Red alerts (dose length products twice the median) were identified and two independent reviewers established whether alerts were true (unjustifiable) or false (justifiable). During the second time period radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…Herein, patient mispositioning “off-center” counted for 30% of the total justification used by our CT radiographers. A similar finding was reported by [ 9 ]. It is well known that patient mispositioning compromises CT tube current modulation function [ 14 ], leading indirectly to increased patient exposure [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Herein, patient mispositioning “off-center” counted for 30% of the total justification used by our CT radiographers. A similar finding was reported by [ 9 ]. It is well known that patient mispositioning compromises CT tube current modulation function [ 14 ], leading indirectly to increased patient exposure [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…While patient size is a mutual finding on both the prospective and retrospective dose management tools, high scan length due to added delay scan or to cover pathology or because of a combined study as well as arms in the field of view were frequently reported in the prospective dose management tool together with technical errors. The justifications reported by our CT radiographers’ using the retrospective (DOET TQM) dose management tool seem to be matching to a certain degree the justification reported by [ 9 ] using their retrospective DoseWatch platform.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…imaging of a wrong body part or imaging the wrong patient). Crowley et al have described the advantages of a radiographer feedback to help in the management of dose alerts [ 23 ].…”
Section: Alerts For Unintended and Accidental Medical Exposuresmentioning
confidence: 99%
“…These tools allowed us to monitor these values during a preselected period, which can help to identify changes in the scanning protocols. They allowed, as well, the export of data for further processing by means of analysis software (Crowley et al 2020).…”
Section: Data Collection and Validationmentioning
confidence: 99%